Determinan Terhadap Struktur Modal Dengan Non Debt Tax Shield Sebagai Moderasi (Studi Pada Perusahaan Properti, Real Estate dan Konstruksi Bangunan Yang Terdaftar Di BEI Periode 2015-2018) - Ana Wijandari (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine the effect of profitability, firm size, business risk, likuidity, and growth opportunity on capital structure and non debt tax shield as moderator. The objects of this study were property, real estate, and construction company sectors listed on the stock exchanges in Indonesia during 2015-2018, with a total of 72 companies. Sampling method used in this research is purposive sampling. The data collected were analyzed by descriptive analysis and statistical analysis using WarpPLS 5.0. The result of the research shows that profitability, business risk, likuidity, growth opportunity, and non debt tax shield have an effect on capital structure, while the firm size is not. Non debt tax shield found not able to moderate the effect of profitability and growth opportunity on capital structure. Non debt tax shield are found as pure to moderate effect of firm size on capital structure and be a quasi to moderate effect of business risk and likuidity on capital structure. Keywords : Profitability, Firm Size, Business Risk, Likuidity, Growth Opportunity, Non Debt Tax Shield, Capital Structure